Upaya Meningkatkan Kemampuan Mengenal Lambang Bilangan Melalui Kegiatan Bermain Kartu Angka pada Anak Kelompok A di SPS Dahlia Jatisampurna Bekasi - Arman Paramansyah; Ahmad Zamakhsari; Ernawati Ernawati (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
This study aims to improve the ability to recognize number symbols in Anak Kelompok A at SPS Dahlia Jatisampurna Bekasi through playing number cards. The ability of number symbols studied included making a sequence of numbers 1-10 with objects, pointing and writing symbols for numbers 1-10, pairing number symbols with objects 1 to 10. Early childhood is a unique individual who has a pattern of growth and physical development, cognitive, socio-emotional, creativity, language and communication specifically in accordance with the stages that are being passed by the child. The research used qualitative research with a descriptive approach. In the process of collecting data, researchers used the methods of observation, interviews, and documentation. The validity of the data in this study includes the test of credibility (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity). The results showed that there was an increase in the ability to recognize number symbols after learning through number card playing activities. As for what the teacher does before carrying out number card learning, namely: Choosing a theme to be achieved, planning or preparing teaching materials to be delivered, dividing children into several groups, explaining how to play number cards, providing opportunities for children to play number cards, repeating material from the last number card learning activity is to carry out an evaluation. Keywords: ability to recognize number symbols, playing number cards, early childhood